2017
DOI: 10.1093/pasj/psw120
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the H ii region and AFGL 333-Ridge: Implications for the star formation scenario

Abstract: We investigated the star formation activities in the AFGL 333 region, which is in the vicinity of the W4 expanding bubble, by conducting NH 3 (1,1), (2,2), and (3,3) mapping observations with the 45 m Nobeyama Radio Telescope at an angular resolution of 75 ′′ . The morphology of the NH 3 (1,1) map shows a bow-shape structure with the size of 2.0 × 0.6 pc as seen in the dust continuum. At the interface between the W4 bubble and the dense NH 3 cloud, the compact HII region G 134.2+0.8, associated with IRAS 02245… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Moore et al (2007) similarly conclude that the W3 molecular cloud has been compressed on one side by the expansion of IC 1805. While infrared sources nestled between the western edge of IC 1805 and eastern edge of the W3 molecular cloud are thought to be the product of this interaction , W3 Main, W3 (OH), and W3 North are thought to be sites of triggered star formation from IC 1795, which is part of W3 as well and not from the expansions of the ionization front (Nakano et al 2017;Jose et al 2016;Kiminki et al 2015). There is therefore uncertainty regarding a physical connection between W3 and IC 1805.…”
Section: The H II Region and Stellar Bubble Associated With The W4 Co...mentioning
confidence: 99%
“…Moore et al (2007) similarly conclude that the W3 molecular cloud has been compressed on one side by the expansion of IC 1805. While infrared sources nestled between the western edge of IC 1805 and eastern edge of the W3 molecular cloud are thought to be the product of this interaction , W3 Main, W3 (OH), and W3 North are thought to be sites of triggered star formation from IC 1795, which is part of W3 as well and not from the expansions of the ionization front (Nakano et al 2017;Jose et al 2016;Kiminki et al 2015). There is therefore uncertainty regarding a physical connection between W3 and IC 1805.…”
Section: The H II Region and Stellar Bubble Associated With The W4 Co...mentioning
confidence: 99%
“…In AFGL 333, outflow candidate 115 was associated with an outflow identified from the CO (2 → 1) line and an H 2 O maser (see Nakano et al 2017). They also suggested that star formation in the AFGL 333 region proceeded without significant external triggers.…”
Section: W3 Complexmentioning
confidence: 97%
“…The AFGL 333 region was investigated by Nakano et al (2017); Liang et al (2021) and will not be dealt with in the present paper. This paper is organized as follows; Section 2 describes the datasets employed and Section 3 gives the results of the present kinematical analysis.…”
Section: The Aim Of the Present Papermentioning
confidence: 99%